2021
DOI: 10.1038/s41467-021-22858-x
|View full text |Cite
|
Sign up to set email alerts
|

The tepary bean genome provides insight into evolution and domestication under heat stress

Abstract: Tepary bean (Phaseolus acutifolis A. Gray), native to the Sonoran Desert, is highly adapted to heat and drought. It is a sister species of common bean (Phaseolus vulgaris L.), the most important legume protein source for direct human consumption, and whose production is threatened by climate change. Here, we report on the tepary genome including exploration of possible mechanisms for resilience to moderate heat stress and a reduced disease resistance gene repertoire, consistent with adaptation to arid and hot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
98
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(103 citation statements)
references
References 105 publications
4
98
1
Order By: Relevance
“…Because of this, a sister species, such as tepary bean ( Phaseolus acutifolius A Gray. ), has recently gained attention in breeding efforts for improving abiotic stress tolerance in common bean [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, a sister species, such as tepary bean ( Phaseolus acutifolius A Gray. ), has recently gained attention in breeding efforts for improving abiotic stress tolerance in common bean [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the Tepary bean represents an important genetic resource to improve resistance to heat and drought stresses, which are the most limiting factors in common bean [12]. Throughout this research, we have demonstrated the potential of this species to contribute outstanding trait scores via interspecific congruity backcrosses with the common bean.…”
Section: Discussionmentioning
confidence: 80%
“…Given the complex nature of the heat and drought tolerances, it is foreseen that the GP and GABC approaches would outperform GWAS-type modeling [61], without meaning that the latter will be incapable to capture variants with moderate effects segregating at medium frequencies, still useful to boost more traditional and scalable marker-assisted backcrossing (MABC) initiatives [62]. Merging these approaches will eventually insight into molecular evolution and pre-breeding under heat and drought stresses [12], both at the yield and ecophysiological levels [63].…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wild forms and wild species should thus be better represented in the collection, with due consideration to the regeneration capacity and disclosure of the potential. There are two points here: first, given the possibilities opened by comparative mapping in the Phaseoleae (Schmutz et al, 2014;Vlasova et al, 2016;Garcia et al, 2021;Moghaddam et al, 2021) and by gene editing (Bhatta and Malla, 2020;Ku and Ha, 2020), it may be time to think beyond direct interspecific hybridization for the use of alien germplasm. In that sense, species of clade A that may represent half of genus (Delgado-Salinas et al, 2006;Porch et al, 2013;Debouck, 2021) may be opportunities of genes to imitate and/or to regulate differently instead of genes to transfer.…”
Section: Discussionmentioning
confidence: 99%